EU organic agriculture: An overview of latest legislative framework - Stelina Rodino (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
For the next decade, one of the objectives of the recently released EU's strategy "Farm to Fork" is to reach a target of 25% in organic food and farming in the EU agriculture. For this target to be accomplished, the overall EU organic area should be increased, by complying with the regulations in force. This paper is an overview of the new set of regulations that will come into force by the beginning of the next year. Starting with 01 January 2022 new organic regulation will apply to all EU states. The latest European Union (EU) rules on organic production and labelling of organic products was adopted on 30 May 2018, by the European Parliament and the Council (2018). The future framework for organic farming is expected to harmonize and simplify the standards for all EU and non-EU farmers marketing their products across Europe. In the same time, it will prevent unfair trade practices while consumer trust in organic production will increase. The entire supply chain will have to comply with the organic measures and a wider list of products are covered. The certification process was also taken into account, enhancing an easier process for the small farmers.
Keywords: L50; Q01; O13; 330; farm to fork; organic agriculture; regulations